The overlooked component in the consumption of counterfeit luxury brands studies: Materialism: A literature review - Trinh, V.; Phau, Ian (Academy of Taiwan Information Systems Research, 2011)
Trade in counterfeit luxury brands is perceived as a challenging issue to the luxury industry. This paper seeks to explore an often overlooked component of consumer behavior in the consumption of counterfeit luxury brands - materialism. An extensive and critical literature review was conducted that included contributions from different streams of management and marketing research. While materialism played an essential role in influencing purchase intention of consumer consumption of luxury brands, little is known about its role in consumption of counterfeit luxury brands. Moreover, the concept of materialism can be further dimensionalised pertaining to the motivation of indulging in counterfeits purchase. By further investigation of the role of materialism in the consumption of counterfeit luxury brands, this paper also opens an agenda of directions worthy of research which will have academic, managerial and social policy significance.